The current status of trauma care for older adults in Saudi Arabia - Naif Harthi; Steve Goodacre; Fiona C. Sampson (Frontiers in Medicine)
The aging population in Saudi Arabia presents unique challenges to the trauma care system, especially in prehospital settings. This narrative review aims to assess the current status of trauma care for older adults in Saudi Arabia, focusing on the implications of aging, gaps in the trauma system, and the role of emergency medical services. The global rise in life expectancy has increased the incidence of injuries among older adults, leading to a greater burden on healthcare systems. The review highlights the complexity of assessing and managing trauma cases in older adults, including the impact of physiological changes on injury outcomes, challenges faced by ambulance workers, and the lack of a robust trauma care infrastructure in Saudi Arabia. Moreover, it identifies gaps in geriatric-specific training and prehospital care pathways that limit effective management. To address these issues, recommendations include enhancing geriatric-specific education for ambulance workers, improving trauma system infrastructure, and conducting further research to explore the impacts of aging on trauma outcomes. These efforts are critical for reducing the healthcare burden and improving trauma care quality for older adults in Saudi Arabia.